(untitled) (Research, Society and Development, 2022)
Justification: There is a solid worldwide call to control the use of antimicrobials associated with new therapeutic approaches against multidrug-resistant infections, such as those caused by the species E. faecalis and E. faecium, commensal opportunistic pathogens usually present in healthcare-related infections (HAI). The high adaptability of these pathogens to the nosocomial environment and the acquisition of resistance and virulence genes are among the main factors contributing to the worsening of these infections. CRISPR-Cas acts as a bacterial defense system, evolutionarily selected due to the association of bacteria with viruses, present in some strains of E. faecalis and E. faecium. It is speculated that CRISPR-Cas could be used in different vectors, including conjugative plasmids, for editing and inactivating resistance genes. Goals: To investigate the use of CRISPR-Cas in conjugative plasmids to control the spread of multidrug-resistant enterococcal strains. Methodology: This is a scope-based review, applying selection criteria and inclusion of studies in the time interval between 2016 and 2021. Conclusion: Molecular editing tools, such as CRISPR-Cas, may be promising alternatives in controlling multidrug-resistant infections and contribute to the control of hospital spread. Strains that do not have this system are more susceptible to acquiring mobile genetic elements, acquiring resistance and virulence genes. The applicability of CRISPR-Cas in conjugative plasmids is an innovative and feasible method, capable of interfering in the mobile genetic elements acquisition, and consequently, reducing resistance and virulence expression, both in the Enterococcus genus and in others.